2016
DOI: 10.1016/j.apsoil.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in activity and structure of the soil microbial community after application of azoxystrobin or pirimicarb and an organic amendment to an agricultural soil

Abstract: Changes in activity and structure of the soil microbial community after application of azoxystrobin or pirimicarb and an organic amendment to an agricultural soil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…This shows that the organic and the inorganic soil amendments acted as pH lowering (neutralizing) substances from acidity to alkalinity. The huge pH changes of almost two units may imply that the soil in question had very low buffer capacity, making the amendments to be quite The findings of this study conform with those of Álvarez et al [16] who reported an increase in soil pH after application of the organic amendments. The increase of the soil pH to 6.70 considered conducive since the values remains close to neutrality which implies that most of the crops can thrive well in such near-neutral levels.…”
Section: Influence Of Organic and Inorganic Amendments On Soil Phsupporting
confidence: 89%
“…This shows that the organic and the inorganic soil amendments acted as pH lowering (neutralizing) substances from acidity to alkalinity. The huge pH changes of almost two units may imply that the soil in question had very low buffer capacity, making the amendments to be quite The findings of this study conform with those of Álvarez et al [16] who reported an increase in soil pH after application of the organic amendments. The increase of the soil pH to 6.70 considered conducive since the values remains close to neutrality which implies that most of the crops can thrive well in such near-neutral levels.…”
Section: Influence Of Organic and Inorganic Amendments On Soil Phsupporting
confidence: 89%
“…This effect was observed for IBF and KTP at the beginning of the experiment; however, the stimulation of this activity was found at the subsequent sampling times. Since the chemical structure and physico-chemical properties of the organic compounds determine their toxicity to microorganisms, their effects on soil respiration were found to be extremely diversified (Liu et al, 2009; Kotzerke et al, 2011; Conkle and White, 2012; Cycoń and Piotrowska-Seget, 2015; Álvarez-Martín et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, both SMS and pesticides affect soil microbial communities, which may have different effects on soil quality. Therefore, Álvarez-Martín et al [ 60 ] studied the modifications of soil microbial communities in an agricultural soil amended with SMS at rates of 2% and 5% w / w , and treated with the pesticides azoxystrobin or pirimicarb applied at 2 and 25 mg·kg −1 rates ( Table 5 ). The dissipation rate of azoxystrobin was lower than that of pirimicarb after 90 days in both unamended and amended soils.…”
Section: Application Of Sms To Soils and Its Effect On The Behaviomentioning
confidence: 99%